GENETIC VARIABILITY AND SEASONAL INFLUENCE OF FALL ARMYWORM (SPODOPTERA FRUGIPERDA (J. E. SMITH)) DAMAGE TO EARLY VEGETATIVE GROWTH OF AFRICAN MAIZE ACCESSIONS IN THE HUMID TROPICS OF SOUTH-EASTERN NIGERIA - E. Obok; M. Ittah; I. Udo; E. Ojubi; J. Ulafor; S. Umoetok (Journal of Animal and Plant Sciences, 2020)
Fall armyworm (Spodoptera  frugiperda (J. E. Smith)) (FAW) is a petrifying invasive pest of maize (Zea mays L.) in Africa. Ten tropical maize accessions from the International Plant Genetic Resources Institute (IPGRI) collections and a check (Ikom White variety) were studied, under rainfed conditions, in a multi-environment trial (MET) to assess their responses to natural infestation of FAW. The study was conducted in the 2018 first and second maize cropping seasons in Cross River State, Nigeria using a genotype x season interaction (GSI) model. The combined analyses of variance showed non-significant difference (p > 0.05) for genotypes and significant (p ≤ 0.05) genotype x season interactions for seedling emergence, plant height, number of leaves, leaf area and FAW infestation. The most FAW-damaged maize accession in this study was TZm-304 while TZm-1427 was the least FAW-damaged maize accession. Overall, FAW infestation was significantly (p ≤ 0.01) higher in the second maize cropping season (Akpabuyo) than in first maize cropping season (Calabar). This subsequently led to corresponding decreases in early vegetative growth in the second maize cropping season. The IPGRI African maize accessions evaluated in this study were all susceptible to FAW damage at their early vegetative growth stages. However, the infestation dynamics of FAW on maize in Africa is presently being understudied. Thus, there is a dire need for the adoption of a genotype x location x year (GLY) model in subsequent MET studies on FAW across all maize-growing States in Nigeria and selection for maize genotypes in breeding for resistance to FAW should consider early vegetative growth stage and initial establishments in the field as useful aids to selection.
Keywords: Fall armyworm; Ikom White; IPGRI; maize; multi-environment trial; Nigeria